Pengaruh GDP, Suku Bunga, dan Upah Minimum Terhadap Penyerapan Tenaga Kerja di Indonesia - Selvianti, Selvianti; Rahman, Abdul (Economics and Digital Business Review, 2023)
The purpose of this study is to determine the effect of GDP, interest rates, and minimum wages in absorbing workers in Indonesia. The study uses independent variables in the form of GDP, interest rates, and minimum wages with the dependent variable being employment. The type of approach taken is a quantitative approach with a time series of 1997-2021 collected from the BPS website, SIMREG Indonesia, books or literature and reports that have a correlation. The method of analysis in the preparation of this work is multiple linear regression analysis using SPSS version 26. The researcher concluded that (1) employment is significantly affected by GDP; (2) employment is not significantly affected by interest rates; (3) labor absorption is significantly influenced by the minimum wage